Antioxidant and anti-inflammatory activities contribute to the prophylactic effect of semi-purified fractions obtained from the crude methanol extract of Muntingia calabura leaves against gastric ulceration in rats. (22nd April 2015) - Balan, Tavamani; Sani, Mohd. Hijaz Mohd; Mumtaz Ahmad, Salahuddin Haji; Suppaiah, Velan; Mohtarrudin, Norhafizah; Zakaria, Zainul Amiruddin
Abstract: Ethnopharmacological relevance: In traditional medicine, the leaves, flowers, barks and roots of Muntingia calabura L. (Muntingiaceae) have been employed as a treatment for various ailments including dyspepsia and to relieve pain caused by gastritis and peptic ulcer disease. The methanolic extract of Muntingia calabura leaves (MEMC) has been proven in the previous study to possess significant antiulcer activity. In this study, we attempted to determine the prophylactic effect of the fractions obtained from MEMC against ethanol-induced gastric lesion in rats and the involvement of antioxidants and anti-inflammatory mediators. Materials and methods: The MEMC was fractionated with petroleum ether (PEF), ethyl acetate (EAF) and distilled water (AQF). These fractions were investigated for possible antiulcer property using ethanol-induced gastric ulcer rat model. The rats were administered orally once daily with 8% Tween 80 (control), 100 mg/kg ranitidine, or the fractions, in the doses of 100, 250, and 500 mg/kg, for 7 days, followed by ulcer induction using absolute ethanol. The rats were euthanized; macroscopic and histological observations of the stomach were done. The ulcer area (UA) was determined and the percentage protection afforded by the fractions was calculated. The fractions were subjected to antioxidant studies including the superoxide and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, oxygen radical absorbance capacity (ORAC) and total phenolic content (TPC) assay. Involvement of nitric oxide (NO) and inflammatory mediators such as lipoxygenase (LOX) and xanthine oxidase (XO) were evaluated. Phytochemical screening and HPLC analysis of the fractions were also conducted. Results: Pre-treatment of PEF and EAF significantly ( p <0.001) attenuated the gastric lesions as compared to the control group in a dose-dependent manner. On the other hand, 100 and 250 mg/kg of AQF significantly ( p <0.001) prevented the ulcer formation but at the highest dose (500 mg/kg), AQF failed to significantly reduce the ulcer formation, showing a dose-independent antiulcerative effect of AQF. The histological evaluation supported the observed gastroprotective activity of PEF, EAF and AQF. All the fractions showed high superoxide and DPPH scavenging activity, meanwhile the EAF showed highest TPC followed by PEF and AQF. These fractions also significantly ( p <0.05) inhibited the NO while maintaining the viability of the cells. EAF exhibited high inhibition towards both the LOX and XO enzymes, meanwhile PEF and AQF exerted high LOX inhibition but low XO inhibition. Phytochemical screening and HPLC profiling suggested the presence of flavonoid- and tannin based compounds in PEF and EAF. Conclusion: It can be concluded that the prophylactic effect of the fractions on gastric ulceration in rats is associated with its high antioxidant activity and its ability to effectively inhibit the inflammation mediators. Presence of several flavonoids and gallic acid explains the effectiveness of the fractions in affording protection against gastric damages. Graphical abstract: